ATYPICAL MICROGLANDULAR ADENOSIS MIMICKING INVASIVE TUBULAR CARCINOMA, A RARE CHALLENGING DIAGNOSIS - Hera Novianti; Fitri Nur Handriyani; Aswiyanti Asri; Yenita Yenita; Noza Hilbertina; Pamelia Mayorita; Yessy Setiawati; Zulda Musyarifah; Meta Zulyati Oktora; Maisyah Nelzima (Nusantara Hasana Journal, 2024)
Background: Microglandular adenosis (MGA) is a rare breast lesion that poses diagnostic challenges due to its resemblance to invasive carcinoma, particularly invasive tubular carcinoma (ITC). Atypical MGA is of clinical concern because of its potential for malignant transformation. Accurate diagnosis relies on histopathological examination and immunohistochemical (IHC) analysis. Case Presentation: A 34-year-old woman presented with a painless lump in her left breast. Intraoperative frozen section analysis revealed small glandular structures with histological features mimicking ITC. Definitive diagnosis required further evaluation. Immunohistochemical analysis demonstrated S100 positivity, consistent with glandular differentiation, and negative p63 staining, indicating the absence of a myoepithelial layer. These findings, in the absence of definitive stromal invasion, supported a diagnosis of atypical MGA. Complete surgical excision was performed to ensure negative margins and exclude associated malignancy. Discussion: This case highlights the diagnostic complexity of atypical MGA, particularly in young patients. Frozen section analysis alone often fails to distinguish MGA from invasive carcinoma due to overlapping histological features. IHC markers, such as S100 and p63, are critical for differentiation. S100 positivity confirms glandular origin, while p63 negativity indicates the lack of a myoepithelial layer, distinguishing MGA from benign proliferative lesions. Accurate diagnosis is essential to avoid overtreatment, such as unnecessary chemotherapy or radical surgery, while ensuring appropriate management to mitigate malignant potential. Conclusion: This report underscores the importance of combining frozen section and IHC findings for rare breast lesions like atypical MGA. Increased awareness and careful evaluation are essential to achieve timely and precise diagnosis, enabling optimal surgical management and long-term outcomes.